A Parametric Study of Solute Redistribution During Transient Liquid Phase Diffusion Bonding Process. (2001) - Jen Jen, Tien-Chien Tien-Chien; Jiao Jiao, Yuning Yuning; Hwang Hwang, Thomas Thomas
Abstract : A parametric study is performed to investigate the solute redistribution during the transient liquid phase (TLP) diffusion bonding process. The macroscopic solute diffusion in the liquid and the solid phase, as well as the solid transformation to the liquid due to solute macrosegregation, are considered in this study. The effects of the following parameters are considered: ratio of solute diffusivity in liquid and solid state alloy( ξ = D l / D s ), holding temperatures( θ ), a combined parameter related to solidus and liquidus slopes in the phase diagram( ϕ ), and the re-melting and re-solidification time( τ ) . The thickness of the pure liquid zone and the mushy zone of the TLP diffusion bonding process are demonstrated with respect to the above-mentioned parameters. It is shown numerically that the holding time, the holding temperature, and solute diffusivity ratio influence the solute distribution strongly, which in turn influences the liquid zone and mushy zone thickness significantly. It is concluded that for the TLP diffusion bonding process, the optimal technique parameters are high holding temperature, long holding time, and a large liquidus and solidus temperature slope ratio( m l / m s ) of the interlayer material.